Sundanese Culture Education Strategy at SMAN 1 Depok - Al Asskari, Fernandez Rayhan (UI Scholars Hub, 2025)
This study aims to analyze and evaluate the effectiveness of Sundanese cultural education strategies implemented at SMA 1 Depok. This research uses a qualitativeapproach with data collection techniques in the form of observation, interviews, and documentation studies. The respondents of the study were students and teachers at SMA1 Depok who were involved in Sundanese cultural education programs. The results showed that the Sundanese cultural education strategy implemented at SMA 1 Depok has succeeded in increasing students' understanding of Sundanese culture. Students show a high interest in learning Sundanese culture and expressing it in various cultural activities at school. Teachers also find it helpful with this program and state that this program can help increase students' interest in learning Sundanese culture.